Factors Associated with Singleton Preterm Birth in Shire Suhul General Hospital, Northern Ethiopia, 2018. (8th May 2019) - Kelkay, Bayew; Omer, Awol; Teferi, Yelfu; Moges, Yohannes
Abstract : Background. Preterm birth is the leading cause of neonatal mortality and significant health consequences to the newborn, families, and communities and tens of emotional and economic costs. Therefore, the aim of this study was to assess the magnitude of singleton preterm birth and associated factors in Shire Suhul General Hospital, Northern Ethiopia. Methods. Institutional based cross-sectional study was conducted among systematically selected 325 postnatal mothers in Shire Suhul General Hospital, Northern Ethiopia, from January to March 2018. The data were collected through both face-to-face interview and chart review by using pretested semistructured questionnaires. SPSS version 20 was employed to enter and analyze the data. Both bivariate and multivariate logistic regression models were run to identify factors associated with singleton preterm birth at the level of P values ≤ 0.25 and <0.05 for each model, respectively. Result. The magnitude of singleton preterm birth in Suhul Hospital was 16.9%. Smoking cigarette/drinking alcohol during pregnancy[ AOR=3.61: CI 95%; 1.59-8.23], previous abortion[ AOR=2.37: CI 95%; 1.15-4.88], hemoglobin level < 11gm/dl[ AOR=2.44: CI 95%; 1.14-5.22], visible physical neonatal congenital anomaly[ AOR=10.42: CI 95%; 1.66-65.23], and history of giving low birth weight baby[ AOR: 2.78 CI 95%; 1.39-5.55] were the factors statistically associated with singleton preterm birth. Conclusion. The magnitude of preterm birth in this study was higher than the average prevalence of preterm birth reported in Ethiopia. Smoking cigarette/drinking alcohol during pregnancy, mothers who had previous abortion, low maternal hemoglobin level, presence of visible physical congenital anomalies of newborn baby, and history of bearing low birth weight baby were found to have statistically significant association with singleton preterm birth. Supplement of daily iron with folic acid (folic acid ideally before pregnancy) for all pregnant mothers with good adherence monitoring and giving attention to preconceptional health care service to avoid any cigarette smoking/alcohol drinking and risk detection were set as recommendations.